The double life of the family - Bittman, Michael. (Allen and Unwin, 1997)
Is the myth of the nuclear family dead? The other life of the family. The rise of intimacy. Working for nothing. At home: the more things change, the more they stay the same. Pseudomutuality: the disjunction between domestic inequality and the ideal of equality...